Electrospun nanostructures for solar energy harvesting and motion sensing - Ma, Shaoyang (2019)
With the rapid development of human technology, we are continuously facing new problems and challenges. On one hand is the limited natural resources, and on the other hand is the increasing demands for convenient lifestyle. It is not a good idea to sacrifice one aspect to satisfy the other, but we should seek a balance between sustainable development and the comfortable living concept. Thus it becomes a very crucial task to explore the low cost, large scale and environmental friendly fabrication methods for wide applications.